Facile One-Step Dynamic Hydrothermal Synthesis of Spinel LiMn(2)O(4)/Carbon Nanotubes Composite as Cathode Material for Lithium-Ion Batteries - Shen, Chaoqi (Materials (Basel), 2019)
Nano-sized spinel LiMn(2)O(4)/carbon nanotubes (LMO/CNTs) composite is facilely synthesized via a one-step dynamic hydrothermal approach. The characterizations and electrochemical measurements reveal that LiMn(2)O(4) particles with narrow size distribution are well dispersed with CNTs in the composite. The LMO/CNTs nanocomposite with 5 wt % CNTs displays a high specific discharge capacity of 114 mAh g(−1) at 1C rate, and the retention rate after 180 cycles at room temperature reaches 94.5% in the potential window of 3.3 to 4.3 V vs. Li/Li(+). Furthermore, the electrochemical performance of the composite with 5 wt % CNTs at elevated temperature (55 °C) is also impressive, 90% discharging capacity could be maintained after 100 cycles at 1C. Such excellent electrochemical performance of the final product is attributed to the content of CNTs added in the hydrothermal process and small particle size inherited from pretreated MnO(2) precursor.